A decadência ideológica, cinismo e niilismo: Machado e Brecht - Nascimento, Luciana Rodrigues do (2023)
Ideological decadence, cynicism, and nihilism are devices present in some of Machado de Assis' satirical and Bertolt Brecht's epic works. The general objective of this thesis is to highlight that art is inseparable from the contradictions of society divided into distinct social classes: dominant and dominated. Thus, in the works of the aforementioned authors it is possible to find such devices that enable a more critical understanding of society.